Drying shrinkage, strength and microstructure of alkali-activated high-calcium fly ash using FGD-gypsum and dolomite as expansive additive. (November 2020) - Hanjitsuwan, Sakonwan; Injorhor, Borwonrak; Phoo-ngernkham, Tanakorn; Damrongwiriyanupap, Nattapong; Li, Long-Yuan; Sukontasukkul, Piti; Chindaprasirt, Prinya
Abstract: This paper aims to investigate drying shrinkage, strength and microstructure of alkali-activated high-calcium fly ash (AAHF) paste by using FGD-gypsum (FGD) and dolomite (DLM) as expansive additives. The 10 M sodium hydroxide combined with sodium silicate solutions were used as alkaline activator for all mixes. The preparation of AAHF paste was divided into 2 steps. First, the study focused on the effects of expansive additive (FGD and DLM) and liquid/binder (L/B) ratio on the drying shrinkage of AAHF paste. The fly ash (HF) was replaced with FGD and DLM at the dosages of 0%, 2.5%, 5.0%, 7.5%, and 10% by weight of binder. The drying shrinkage, setting time, compressive strength and microstructure of AAHF paste containing FGD and DLM were studies. Test results showed that the use of FGD and DLM as expansive additives improved the drying shrinkage of AAHF paste. The increasing L/B ratio had an adverse effect on drying shrinkage. The setting time of AAHF paste containing FGD and DLM decreased, whereas the strength increased. However, the strength development of the AAHF paste incorporated with FGD tended to decline at the curing time of 120 days. The increase in strength was due to the formation of some strength-bearing chemical phases which was demonstrated by the XRD, FTIR, and SEM/EDS analyses. The differences in reaction products were an essential factor in the strength development of the AAHF paste with expansive additive. It can be recommended that using DLM was advantages regarding the improvement of drying shrinkage and long-term strength in comparison with the AAHF paste with FGD.